Na+ and K+ body levels and survival of fingerlings of Rhamdia quelen (Siluriformes, Pimelodidae) exposed to acute changes of water pH - Maria Ignez Zaions (Ciência Rural, 2000)
The objective of this study was to investigate the effect of water pH on survival and Na+ and K+ body levels of fingerlings of Rhamdia quelen, a freshwater catfish. Survival was 100% at pH 4.00 to 9.0 throughout the experiment (96h), and death of all fingerlings was observed only at pH 3.75 or lower and at pH 10.50. There was a significant correlation between water pH and body Na+ levels (but not K+ levels) 72h after transfer. There was a clear reduction in Na+ levels when the transfer was to pH outside the 5.0 - 9.0 range, which is in agreement with the fact that fishes exposed to such pHs present loss of ions by diffusion and/or a decrease in absorption. Growth experiments with this species probably would present best results within the 5.0 - 9.0 pH range, in which the decrease of body Na+ levels is reduced.